Comprehensive study of SNAREs involved in the post-Golgi transport in Drosophila photoreceptors - Yuka Ochi; Hitomi Yamashita; Shogo Sasaki; Takumi Ogawa; Yumi Yamada; Tatsuya Tago; Takunori Satoh; Akiko K. Satoh (Frontiers in Cell and Developmental Biology)
Polarized transport is essential for the construction of multiple plasma membrane domains within cells. Drosophila photoreceptors serve as excellent model systems for studying the mechanisms of polarized transport. We conducted a comprehensive soluble N-ethylmaleimide-sensitive factor attachment protein receptor (SNARE) screening of the fly genome using RNAi knockdown and CRISPR/Cas9 somatic knockout combined with the CoinFLP system to identify SNAREs involved in post-Golgi trafficking. The results suggest that in post-Golgi transport, no SNARE is exclusively responsible for transport to a single specific plasma membrane domain. However, each SNARE shows some preference for certain membrane domains: the loss of nSyb, Ykt6, and Snap24/25 results in severe defects in rhabdomere transport, while the loss of Syx1A and Snap29 leads to significant impairments in basolateral transport. Together with the function of Syx1A, Snap25, and nSyb in the fusion of synaptic vesicles with the synaptic plasma membrane, these results suggest that SNAREs are not the sole determinants for vesicles to specify their target subdomains in the plasma membrane. Furthermore, rhodopsin transport to the rhabdomere requires two kinds of R-SNAREs, Ykt6 and nSyb, suggesting that multiple sets of post-Golgi SNAREs contribute in tandem or in cooperation, rather than in parallel.